Social media and students' learning - Marković Marija; Stanisavljević-Petrović Zorica (Univerzitetska Misao, 2024)
Alongside the development of social media, their implementation in the field of higher education has become more common, raising questions about the relationship between youth and new technologies, as well as the impact of social media on the academic performance of students. The aim of this research is to examine students' perceptions of the effects of social media on the learning process. The research utilized a descriptive research method and a scaling technique, with a custom-constructed Likert scale instrument used for data collection. The research sample was purposive, comprising 314 students from the Faculty of Philosophy at the University of Niš, from various study programs. The results show that students generally have a positive attitude towards the impact of social media on the learning process. Regarding the independent variables in the research, statistically significant differences in responses were observed concerning the variables of affiliation to a study program and the frequency of social media access. The pedagogical implications of this research are related to the possibilities for improving teaching practices in higher education institutions by introducing new media technologies, along with initiatives that support effective learning and greater development of students' digital competencies.